THE INFLUENCE OF CROSS-CULTURAL COMMUNICATION STRATEGY ON EMPLOYEE PERFORMANCE OF PT. MASS RAPID TRANSIT JAKARTA - Saskita Anzelia Indrawati; Catur Nugroho (RADJA PUBLIKA, 2025)
Cross-cultural communication that occurs in the company runs well, both between leaders and employees and between employees. The differences in language of expatriate leaders can be understood by employees, because leaders sometimes use English to communicate. According to interviews with administrative staff, language skills in cross-cultural communication carried out by Japanese expatriate leaders often become an obstacle for all existing employees, causing communication misunderstandings and ineffective employee performance. This research method is quantitative with a descriptive approach. The population in this study were 760 MRT employees. Based on the results of the calculation using the Solvin formula, the sample in this study was 88 people. Based on the results of the study, it can be concluded that there is a significant influence between cross-cultural communication strategies on employee performance at PT. Mass Rapid Transit Jakarta. Based on the Determination Coefficient Table (R2) shows the contribution of the influence of Cross-Cultural Communication Strategies on Employee Performance of 16.3%.